이창동 작가론 : 윤리를 창조하는 '반복'으로서의 영화 만들기 - 이현승; 송정아; Lee, Hyun-Seung; Song, Jeang-Ah (한국콘텐츠학회 논문지, 12(2), 2012)
As a film maker, Lee Chang Dong stands out from most Korean film makers who work within the trappings of genre films. To be sure, Lee has also used the trappings of genre films, such as noire and melodrama, but primarily as a tool to communicate with film audience. In his most recent film "Poetry", Lee seems to have even stripped even the minimal trappings of genre film. Lee commands the audience to self-reflect and work towards their own conclusions by denying them the illusory identification on screen. In this way, Lee's works are counter cinema. Lee achieves a distancing effect using such filmic apparatuses as hand-held camera, fantasy, mise en abyme, and returned gaze. Through these filmic apparatuses, Lee exposes the re-presentation of text and compels his audience to see the historical and political contexts of the text. In this study, I make the case that Lee Chang Dong's film making is an act of repetition compulsion that cultivates ethical reflection, through symbolization of the invisible realities. 영화작가로서 이창동은 장르적 자장 안에서 영화를 만들고 있는 한국영화계의 대다수 감독들과 구별된다. 그동안 그의 영화는 관객과의 소통을 위해 느와르, 멜로 등의 장르를 차용해왔지만 최근작 <시>에 이르러서는 장르적 외피를 벗어던진 것처럼 보인다. <초록물고기>부터 <시>에 이르기까지 일관되게 남은 것은 관객의 참여를 요하는 깊은 심도와 시간의 연속을 암시하는 길게 찍은 숏들의 몽타주, 현실성을 강조한 연기 등 리얼리즘적 표현방식이다. 또한 이창동의 영화들은 환영적 동일시를 깨는 방식으로 관객들에게 성찰의 자리를 돌려준다는 측면에서 장르영화의 카운터 시네마로 파악할 수 있다. 이창동의 영화에서 볼 수 있는 '낯설게 하기'는 핸드헬드, 판타지, 미장아빔, 응시 되돌려 보내기 등의 영화적 장치로 구현된다. 이 장치들은 텍스트의 재현양식을 폭로함으로써 관객들이 역사적, 정치적 컨텍스트를 성찰하게 한다. 본 연구에서는 <시>,<오아시스>,<밀양> 등의 분석을 통해 이창동의 영화 만들기 행위는 결국 보이지 않는 '실재'를 상징화함으로써 '윤리를 창조하는 반복충동'이라고 주장할 것이다.